Лабораторные исследования электропривода электромобиля с суперконденсаторной батареей - Клепиков, Владимир Борисович; Гончар, Александр Сергеевич; Моисеев, Александр Николаевич; Семиков, Алексей Владимирович; Малетин, Ю. А.; Жихарев, Андрей Николаевич (НТУ "ХПИ", 2013)
A special laboratory stand to assay the operation of the proposed scheme of the electric vehicle electric drive with a direct current motor is created. The scheme provides for energy regenerative in braking modes into supercapacitor module. Operability of scheme and the ability of the supercapacitor module to perform the functions of energy storage are confirmed, which allowed to return more than 20% of the expended in acceleration energy in the experiments.
Keywords: мировые автопроизводители; лабораторный стенд электропривода электромобиля; двигатель постоянного тока; рекуперация энергии; суперконденсаторный модуль; накопитель энергии